2008
DOI: 10.1016/j.yjmcc.2008.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide signaling and the regulation of myocardial function

Abstract: Nitric oxide, which is produced endogenously within cardiac myocytes by three distinct isoforms of nitric oxide synthase, is a key regulator of myocardial function. This review will focus on the regulation of myocardial function by each nitric oxide synthase isoform during health and disease, with a specific emphasis on the proposed end-targets and signaling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(105 citation statements)
references
References 117 publications
(182 reference statements)
1
101
0
2
Order By: Relevance
“…Upon eNOS activation and NO binding to soluble guanylyl cyclase, PKG-induced phosphorylation of contractile protein machinery is induced (165). These effects of Epo were confirmed for isolated cells as well as in vivo in hearts after intravenous Epo administration.…”
Section: Epor In the Heartmentioning
confidence: 59%
“…Upon eNOS activation and NO binding to soluble guanylyl cyclase, PKG-induced phosphorylation of contractile protein machinery is induced (165). These effects of Epo were confirmed for isolated cells as well as in vivo in hearts after intravenous Epo administration.…”
Section: Epor In the Heartmentioning
confidence: 59%
“…The role of NO generation by cardiomyocytes and the expression of NOS isoforms is still unclear. Cardiomyocytes have been reported to express two NOS isoforms , endothelial and inducible, in disease states [8][9][10] . It was also reported that cardiac cells express neither iNOS nor eNOS immunoreactivity in both infracted and normal myocardium [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…(5) NO is a key regulator of excitationcontraction coupling in the cardiomyocytes and therefore of myocardial contractile function. (17) NO has also been shown to modulate heart rate, ß-adrenergic inotropic response, myocardial energetics and substrate metabolism. (12) NO effects are achieved via intracellular downstream mechanisms that have initially been thought to be mainly cyclic GMP (cGMP)-mediated, although it is now known that many of the effects of NO are cGMP-independent.…”
Section: Cardiac Endotheliummentioning
confidence: 99%
“…(12) NO effects are achieved via intracellular downstream mechanisms that have initially been thought to be mainly cyclic GMP (cGMP)-mediated, although it is now known that many of the effects of NO are cGMP-independent. (17) The contractile effects of NO depend on the intracellular location of its release and the end-targets of its signalling pathways, e.g. when NO signalling targets the L-type calcium channels in cardiomyocytes, a decreased calcium current ensues which leads to attenuated ß-adrenergic receptor stimulated contraction.…”
Section: Cardiac Endotheliummentioning
confidence: 99%
See 1 more Smart Citation